2000
DOI: 10.1038/sj.jhh.1000959
|View full text |Cite
|
Sign up to set email alerts
|

Role of erythropoietin in cortisol-induced hypertension

Abstract: The mechanism of cortisol-induced hypertension remains unknown. We investigated a possible role of erythropoietin (EPO) as a mediator of hypertension in healthy male subjects treated with cortisol. In Study 1, blood pressure (BP) and serum EPO concentrations were measured on alternate days in nine subjects treated with 80 mg of cortisol per day for 5 days. In Study 2 the same parameters were measured in eight subjects randomised to cortisol (80 mg/day) or placebo and 10 subjects randomised to cortisol (200 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 13 publications
0
26
1
Order By: Relevance
“…Accordingly, treatment of healthy subjects with corticosteroids resulted in a significant increase of serum Epo concentrations. 46 Finally, since an impaired Epo formation in comparison to the degree of ACD was not always observed, especially in children, 43,44 one might suggest that children may harbor a greater capacity than adults to compensate the inhibitory effects of cytokines toward Epo production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, treatment of healthy subjects with corticosteroids resulted in a significant increase of serum Epo concentrations. 46 Finally, since an impaired Epo formation in comparison to the degree of ACD was not always observed, especially in children, 43,44 one might suggest that children may harbor a greater capacity than adults to compensate the inhibitory effects of cytokines toward Epo production.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, treatment of healthy subjects with corticosteroids resulted in a significant increase of serum Epo concentrations. 46 Finally, since an impaired Epo formation in comparison to the degree of ACD was not always observed, especially in children, 43,44 one might suggest that children may harbor a greater capacity than adults to compensate the inhibitory effects of cytokines toward Epo production.Interestingly, we found that in patients with HS, Epo levels were even higher than in IDA subjects although they had comparable hemoglobin levels. In contrast to IDA subjects, HS patients had normal iron levels and no hypoferremia, which indicates that hypoxia as a consequence of anemia rather than iron deficiency is the primary driving force for Epo formation in the kidneys of anemic patients.…”
mentioning
confidence: 99%
“…In fact, extensive in vitro studies have shown that glucocorticoids potentiate erythropoiesis (4,18), enhance proliferation and self-renewal of erythroid progenitors (1), stimulate erythropoietin (19) and cooperate with its effects on progenitor cells (20,21). Further, glucocorticoids are essential to stress erythropoiesis as glucocorticoid receptor-deficient mice are unable to mount an adequate erythroid response to hypoxia or blood loss, both in terms of erythroid-colony Normal ranges are represented by the grey area.…”
Section: Discussionmentioning
confidence: 99%
“…GCs can induce hepatic synthesis of angiotensinogen, increase angiotensin II receptor type 1 concentration in the brain and peripheral tissue and enhance both angiotensin II-stimulated inositol phosphate-3 production in vascular smooth muscle cells and its central actions (159,161). GC-induced increase of erythropoietin contributes to vasoconstriction and therefore hypertension (162). Endothelin has been found to be increased in CS patients (163).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%